A Cross-National Study on Selection Attributes of Instant Noodle between China and Korea. Issue 1 (2nd January 2020) - Cha, Seong Soo; Wang, Xiao-Wu
ABSTRACT: This study aims to determine the important selection attributes of instant noodles that significantly affect consumer satisfaction in Korea and China. Several factors such as taste, price, quality, design, and brand were tested, and the relationships between satisfaction and repurchase intention were analyzed. Based on previous studies, it was found that the importance of selection attributes for instant noodle is taste, price, quality, design, and brand. Using structural equation modeling, 1, 027 questionnaires were surveyed for a statistical method of examining the proposed hypotheses in China and Korea. Results of the study reveal that the importance of selection attributes affected satisfaction significantly. Furthermore, the path coefficient of satisfaction that leads to repurchase was found to be significant. However, consumers' perceived importance of selection attributes of instant noodles varied according to the countries. The path coefficients from taste to satisfaction were more significant for Korean consumers (β = 0.542) than for Chinese consumers (β = 0.359). Meanwhile, the path coefficient from corporate brand to satisfaction was more significant for Chinese consumers (β = 0. 305) than Korean consumers (β = 0.218). This study analyzes the significant selection attributes of instant noodles, the results provide meaningful implications for instant noodle companies in each country regarding the specific attributes they need to prioritize.